A case study of validation and sample analysis for the determination of zotarolimus in various tissues. (April 2013) - Reimer, M Todd; Wan, Xia; Zhang, Jun
Background: Biodistribution of drug and drug candidates offers critical information regarding drug disposition in target and nontarget tissues. Concentrations of therapeutic agents in target tissue provide the foundation for efficacy, while concentrations in nontarget tissue pose potential safety risks. Analysis of tissue samples can sometimes provide important information during the development of a drug candidate, especially at early stages when radio labeled drug material is not readily available.Results: Determining the appropriate approach to allow for accurate, precise and reproducible drug concentration measurements from tissue samples requires addressing issues not present in routinely analyzed biological matrices, that is, plasma. We present here the issues encountered and techniques applied during the development, validation and application of a method for the determination of zotarolimus in a variety of tissues.Conclusion: When well controlled, analysis of tissue samples can be performed in a manner similar to liquid biological matrices.